Menangkal Stunting dari Desa : Edukasi Gizi dan Pemberdayaan Tanaman Kelakai sebagai Pangan Fungsional Tinggi Zat Besi - Solla, Angelia; Pereiz, Zimon; Oksal, Chuchita, Efriyana; Ratna Sari, Julia, Mesra; Hutabalian, Debby Catur, Gracyela; Heja, Anjelika,; Sabatini, Ornella Arnia, Gusnia Devianti, Felly; Prayoga, Apriyanti, Andika; Tundan, Arisumi Ir L; Dandy, Abdullah, Jonathan (Yayasan Daarul Huda Kruengmane, 2025)
Stunting is a condition of impaired growth in children caused by chronic malnutrition, particularly during the first 1,000 days of life. This issue has become a major global nutrition and health concern with long-term impacts on human resource quality. Therefore, promotive and preventive approaches are essential, one of which is community education. This community service activity aimed to improve knowledge and encourage behavioral changes in preventing and managing stunting through educational outreach and assistance in utilizing kelakai (Stenochlaena palustris) as an iron-rich functional food. The methods included interactive counseling using digital media such as visual presentations and educational banners, as well as direct community assistance in processing kelakai. Evaluation was conducted using pretest and posttest questionnaires to measure participants’ knowledge improvement. The results showed an 87.71% increase in knowledge, categorized as good. This program proved effective in enhancing community understanding of the importance of nutrition and the utilization of local food sources for stunting prevention. In conclusion, this community service initiative provides a positive contribution as a strategy to reduce stunting rates in Central Kalimantan, particularly in Gunung Mas, through improved knowledge, awareness, and the use of nutrient-dense local food resources.